2000
DOI: 10.1128/aac.44.4.1035-1040.2000
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Nontraditional Antimicrobials against Multiresistant Acinetobacter baumannii Strains Isolated in an Intensive Care Unit Outbreak

Abstract: Fifteen multiresistant Acinetobacter baumannii isolates from patients in intensive care units and 14 nonoutbreak strains were tested to determine in vitro activities of nontraditional antimicrobials, including cefepime, meropenem, netilmicin, azithromycin, doxycycline, rifampin, sulbactam, and trovafloxacin. The latter five drugs were further tested against four of the strains for bactericidal or bacteriostatic activity by performing kill-curve studies at 0.5, 1, 2, and 4 times their MICs. In addition, novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 11 publications
3
53
1
3
Order By: Relevance
“…The in vitro (1,4) and in vivo activities of colistin (polymyxin E) suggested that it would be an effective antimicrobial agent against A. baumannii (6,9,11,12,18). However, some polymyxin-resistant strains have been reported (15,16).…”
mentioning
confidence: 99%
“…The in vitro (1,4) and in vivo activities of colistin (polymyxin E) suggested that it would be an effective antimicrobial agent against A. baumannii (6,9,11,12,18). However, some polymyxin-resistant strains have been reported (15,16).…”
mentioning
confidence: 99%
“…is the second most common non-fermenting bacteria isolated from clinical specimen especially in hospital settings [8]. The recent years have seen the emergence of this pathogen in ICUs [7].…”
Section: Discussionmentioning
confidence: 99%
“…En adultos sin meninges inflamadas, la concentraciones máximas de meropenem en el LCR han sido menores (~0,6 µg/mL); sin embargo, las concentraciones obtenidas en el LCR con altas dosis de meropenem (con o sin meninges inflamadas), permiten asegurar la inhibición de las enterobacterias que se manifiestan susceptibles en el antibiograma para este compuesto 10,13 . No obstante, estas concentraciones pueden ser marginales o claramente insuficientes para superar las CIM 90 de meropenem contra P. aeruginosa (CIM 90 ~ 3 µg/mL) o A. baumannii (4 a 6,4 µg/mL), también involucrados como posibles agentes de ventriculitis 10,14,15 . Meropenem ha sido utilizado exitosamente en pacientes con ventriculitis por P. aeruginosa 16 , pero con selección de cepas resistentes in vivo en el manejo de pacientes con ventriculitis por A. baumannii 17 .…”
Section: Tratamiento De Agentes Resistentes Por Vía Sistémica Para Baunclassified
“…Los valores de CIM 90 de sulbactam sobre esta especie se aproximan a 8 µg/mL, sin presentar este compuesto una actividad sinérgica con ampicilina, aunque ha sido utilizado exitosamente en infecciones no severas por este agente 27 . El efecto bactericida de sulbactam sobre A. baumannii es transitorio y resulta ser más pronunciado con concentraciones superiores a la CIM (4 x CIM), las que son difíciles de obtener en el LCR 15 ; ello podría explicar resultados parciales obtenidos en el manejo de infecciones del SNC por esta especie 25 . Las fluoroquinolonas tienen una buena penetración al LCR y no requieren dosis intratecales complementarias.…”
Section: Tratamiento De Agentes Resistentes Por Vía Sistémica Para Baunclassified